THE ROLE OF THE TEACHERS IN DEALING WITH SLOW LEARNERS IN THE MUHAMMADIYAH ELEMENTARY SCHOOL - Ningsih, Septia; Suyatno, Suyatno (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Slow learners need specific attention and education services that suit their condition and situation for them to develop their abilities just like other normal children. Teacher roles can become a significant factor in dealing with slow learners, especially in the learning process. The research aims to find out the teacher roles, as well as the inhibiting and supporting factors in dealing with slow learners at SD Muhammadiyah Danugeran in Yogyakarta. The research is qualitative, with a case study approach. The subjects of the study were the school principal, class teachers, and students chosen using the purposive sampling technique. Data were collected through interviews, observation, and documentation. The collected data was analyzed using an interactive inductive data analysis technique, a model proposed by Miles and Huberman. The result suggests that teachers at SD Muhammadiyah Danunegaran have carried out their roles as demonstrators, class managers, initiators, facilitators, mediators, motivators, and evaluators in dealing with slow learners. Abstrak: Anak-anak slow learner membutuhkan perhatian dan layanan pendidikan sesuai dengan kondisi dan keadaanya. Peran guru menjadi faktor yang sangat penting dalam menangani anak slow learner. Penelitian ini bertujuan untuk mengungkap peran guru dalam menangani anak slow learner di SD Muhammadiyah Danunegaran Yogyakarta. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan studi kasus. Subjek penelitian ini adalah guru kelas dan serta peserta didik slow learner. Subjek penelitian terdiri dari kepala sekolah, guru kelas, dan siswa yang ditentukan berdasarkan teknik purposive sampling. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa Guru di SD Muhammadiyah Danunegaran memiliki peran sebagai sebagai demonstrator, pengelola kelas, inisiator, fasilitator, mediator, motivator, dan evaluator dalam menangani anak slow learner.